Effect of Various Levels of N in Combination with FYM on the Growth and Establishment of Date Palm (Dhakki) Cultivar: Nitrogen Dose for Date Palm Cultivation - Khan, Amanullah; Mansoor, Muhammad; Rashid, Abdur; Aziz, Abdul; Hussain, Nazir; Islam, Zafar (Biological Sciences - PJSIR, 2013)